A Beginner's Guide to Water Management—Muck: Causes and Corrective Actions - Mark V. Hoyer; Daniel E. Canfield Jr.; Mark Brenner (EDIS)
Muck: what it is, how it's distributed in water bodies, how to remove it. Plus the ontogeny of aquatic systems.